Solvatochromism Effect Studies on Electronic Absorption Spectral of Some Hydroxy Tolyl Azo Benzaldehyde dyes. - al-Jabali, Asmaa Muhammad; Hemdan, Sokaina; Ali, Fatma (Journal of natural sciences, life and applied sciences, 2017)
The electronic absorption spectra of some prepared substituted aryl azo compounds were recorded in organic solvents of different polarities. The electronic transitions are assigned. The solvents and substituents effects on the spectral behaviour are studied and interpreted. The solvent induced spectral effects have been analyzed using multiple linear regression technique. The Kamlet-Taft and Catalan’s solvent scales were found to be the most suitable for describing the solvatochromic shifts of the absorption spectra. The solute–solvent interactions were determined based on multilinear solvation energy relationships concept. The phenomena of tautomersim were discussed with the possibility of forming intra and intermolecular hydrogen bonds.
Keywords: Azo Dyes; Absorption Spectra; Organic Solvents; Multiple linear regressions